Authentication of Combretum Indicum Varr. B Flower Against Varr. M with Combined Chemometrics of UV-VIS Spectrophotometric: indonesia - Samsul Hadi; Elvina Astria Agustin; Amalia Khairunnisa; Irawati Irawati; Linda Wahyuni (Institute of Computer Science (IOCS), 2022)
Melati belanda flowers have two varieties that look different, namely from the shape of the flowers. The first variety has the shape of an elongated flower and the second variety has the shape of a rounded flower. So that, this difference in the shape of the flower will allow generating different activities. The purpose of this study was to identify the distinctive spectra of these two varieties. The method used is a fingerprint analysis of UV-VIS spectroscopy combined with chemometrics for the identification and authentication of varieties of Melati belanda. The results of the analysis of PLSR Combretum indicum Varr. B against Combretum indicum Varr. M on a spectrum of 218.86-252.54 nm, The first derivatization of RMSEC 2.39; R2 0.9975; RMSEP 6.92; R2 0.9939 and RMSEC 5.63; R2 0.9868. Meanwhile, with a wavelength of 253,260 – 299,020, a normal model of RMSEC 2.01 was obtained; R2 0.9983; RMSEP 1.89; R2 0.9985 and RMSEC 1; R2 0.9772. So can be concluded below UV-VIS spectroscopic fingerprint analysis combined with chemometrics is able to identify the authentication of the Combretum Indicum Varr. B against the occurrence of adulteration of flowers Combretum Indicum Varr. M at a wavelength of 253.260 – 299.020 nm of normal models.